Star wolf - Lasky, Kathryn (Lasky, Kathryn. Wolves of the Beyond, 2014)
The Ring of Sacred Volcanoes has been destroyed and Faolan is leading his small band of wolves across the ice bridge to the hoped for safety of the Distant Blue--but his old enemy Heep is pursuing him and the icy path ahead is filled with danger.